The association between social cohesion and community disaster resilience: a cross‐sectional study - Mohamed Ludin, Salizar; Rohaizat, Munirah; Arbon, Paul (John Wiley & Sons Ltd, 2019)
A cross‐sectional study design was created, using the Index of Perceived Community Resilience (IPCR) and Buckner’s Index of Cohesion (BIC) to survey 386 flood evacuees from six communities in Kelantan, Malaysia, in 2015. The respondents were mostly female (54.7%); lived in basic housing (95.6%); average income (55.9%); secondary level schooling (81.1%); not involved with community organisations (95.1%), volunteering activities (91.2%), or emergency teams (96.9%); inexperience with injury during flooding (94%); experienced the emergency disaster (61.6%); and their mean age was 49 years old. Overall, respondents scored a high level of community disaster resilience (CDR) (mean 3.9) and social cohesion (mean 3.79). Also, respondents’ housing type, event of injury during disaster, volunteering in post‐disaster activities, and emergency team participation were significantly associated with CDR (p = 0.001– 0.002), organisational involvement (p = 0.016), and emergency disaster experience (p = 0.028) were significantly associated with social cohesion. The Pearson correlation coefficient results mostly showing a moderate, weak, and one with a strong relationship. There is a strong relationship between community participation (CDR) in events and BIC variables (r = 0.529, p = 0.001). Other analysis shows a moderate but significant relationship with BIC; is open to ideas (r = 0.332, p = 0.001); community has similar values/ideas (r = 0.421, p = 0.001); sense of pride (r = 0.389, p = 0.001); strong leadership (r = 0.339, p = 0.001); positive change (r = 0.484, p = 0.001); and able to handle problems (r = 0.454, p = 0.001). Overall, the results show that respondents had high levels of CDR and social cohesion, while the demographic characteristics show the impact of CDR and social cohesion. In conclusion, the data gives original insight into the level of association between social cohesion and disaster resilience, which could be used as a building block in sustainable disaster recovery. There is a need to explore this further on programmes designed to improve social cohesion across communities.